Efeitos do ambiente na germinação e emergência de capim-amargoso resistente e suscetível ao glyphosate - Martins, J. F. [UNESP]; Barroso, A. A.M. [UNESP]; Alves, P. L.C.A. [UNESP] (FapUNIFESP (SciELO), 2017)
Sourgrass is one of the most problematic weeds of Brazil. It is an aggressive species in the allocation of resources from the environment and reported to be glyphosate resistant in several states of the country. This work has aimed to verify environmental effects on seed germination and seedling emergence of sourgrass. Laboratory and field trials were conducted to determine the effects of temperature, light, photoperiod, water availability and depth of burial in germination and emergence of seeds. The maximum germination was greater than 80% for seed originated from resistant plants between 15 and 30 °C. For the susceptible ones, the maximum germination occurred only at 30 °C. Germination occurred for both biotypes independent of the presence of light. The best photoperiod for germination of both biotypes was between 8 and 14 hours. Seeds originated from resistant plants showed higher germination levels at low temperatures in the presence of light and in less water availability. There was no germination from -0,8 MPa for both biotypes. The emergence for both biotypes was low, indicating that seed burial could be used in the management of the species. Seeds from resistant plants showed higher and larger germination in temperatures, water content and depth of burial ranges than from originated from susceptible plants.
Effects of environmental factors on seed germination and emergence of glyphosate resistant and susceptible sourgrass
Keywords: Digitaria insularis; Photoperiod; Seeds; Temperature; Water availability